Sentimentos e conhecimentos de puérperas em face da sífilis congênita neonatal (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2017)
Surveying feelings and awareness of neonatal congenital syphilis among mothers